Magnetic properties and microstructure of cobalt nanoparticles in a polymer film - Park, IW; Yoon, M; Kim, YM; Kim, Y; Yoon, H; Song, HJ; Volkov, V; Avilov, A; Park, YJ (PERGAMON-ELSEVIER SCIENCE LTD, 2003)
Superparamagnetic properties of self-aggregated cobalt nanoparticles in the perfluorinated sulfo-cation membrane (MF-4SK) prepared by ion-exchange method were investigated by transmission electron microscopy (TEM) and superconducting quantum interference device (SQUID) magnetometry at various temperatures. Our experimental results show that cobalt nanoparticles in MF-4SK exhibit superparamagnetic properties above the blocking temperature (T-B), which varies from similar to 80 to similar to 300 K depending on the cobalt concentration at 100 Oe applied field. The average particle radius of 3.8 nm inferred from Langevin function fit for the concentration of 7.8 x 10(19) cobalt atoms per 1 g of polymer film is in good agreement with TEM observation. This experimental evidence suggests that cobalt nanoparticles in the polymer film obey a single-domain theory. The results are discussed in the light of current theory for the superparamagnetic behavior of magnetic nanoparticles. (C) 2003 Elsevier Science Ltd. All rights reserved.
Keywords: SUPERPARAMAGNETIC PROPERTIES; PARTICLES; RELAXATION; CO